1999
DOI: 10.1095/biolreprod61.4.1139
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Regulates Glucose Metabolism Through Lactate Dehydrogenase A Messenger Ribonucleic Acid Expression in Cultured Porcine Sertoli Cells1

Abstract: In a previous work, we reported that lactate dehydrogenase A4 (LDH A4) activity is a key step in the stimulatory effect of epidermal growth factor (EGF) on lactate production in cultured Sertoli cells. Here, we further investigated the regulatory mechanisms involved in EGF action on LDH A mRNA expression. Steady-state levels of LDH A mRNA analyzed by Northern blot hybridization were induced to 2. 9-fold in response to a 36-h incubation with EGF (ED(50) = 4 ng/ml, 0.63 x 10(-9) M). Whether EGF-induced increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…In rat Sertoli cells, variations in LDH activity and in the distribution profile of isozymes are accompanied by an increment in ldh a gene expression after FSH and IL1 treatments (Riera et al 2001). On the other hand, similar results were obtained in porcine Sertoli cells after EGF (Boussouar & Benahmed 1999), IL1 (Nehar et al 1998) and TNF treatments (Nehar et al 1997). The present study shows that bFGF increases LDH activity and the levels of mRNA for the LDH A subunit, suggesting that the LDH isoenzyme system is another potential site of action for bFGF.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In rat Sertoli cells, variations in LDH activity and in the distribution profile of isozymes are accompanied by an increment in ldh a gene expression after FSH and IL1 treatments (Riera et al 2001). On the other hand, similar results were obtained in porcine Sertoli cells after EGF (Boussouar & Benahmed 1999), IL1 (Nehar et al 1998) and TNF treatments (Nehar et al 1997). The present study shows that bFGF increases LDH activity and the levels of mRNA for the LDH A subunit, suggesting that the LDH isoenzyme system is another potential site of action for bFGF.…”
Section: Discussionsupporting
confidence: 59%
“…Facilitated Sertoli cell glucose transport across plasma membrane is mediated by the carrier protein termed glucose transporter 1 (GLUT1), the only glucose transporter so far demonstrated in this cell (Ulisse et al 1992). As for the LDH isoenzyme system, increments in lactate production in Sertoli cells have been correlated with an increase in the LDH5 isoenzyme -containing four subunits A. Glucose transport through the plasma membrane and LDH A mRNA levels are regulated in a distinct manner by FSH (Riera et al 2001), interleukin 1 (IL1) (Nehar et al 1998), tumor necrosis factor-(TNF ) (Nehar et al 1997) and epidermal growth factor (EGF) (Boussouar & Benahmed 1999) -factors that modify Sertoli cell lactate production. No data are available on the mechanisms involved in the recently described effect of bFGF on lactate production (Schteingart et al 1999).…”
Section: Introductionmentioning
confidence: 93%
“…Grootegoed et al showed the conversion of glucose to lactate by Sertoli cells (27). This locally produced lactate is augmented by paracrine/autocrine factors such as transforming growth factor β, epidermal growth factor, basic fibroblast growth factor, tumor necrosis factor α and interleukin 1α (28)(29)(30)(31)(32), which are involved in cell-cell communications in the testis (33). These factors target glucose uptake and total LDH activity for stimulating lactate production.…”
Section: Discussionmentioning
confidence: 99%
“…25) Indeed, it was reported that spermatids produce factors that increase the level of lactate production in Sertoli cells and stimulate lactate production and LDHA expression in Sertoli cells. 26,27) The levels of Spag4 expression were also measured to determine the factors involved in the enhanced testicular toxicity of DEHP. Taken together, it was reported that the Spag4 mRNA levels were significantly lower in the testes chronically exposed to DBP than in the controls.…”
Section: Discussionmentioning
confidence: 99%